A Regio- and Stereodivergent Route to All Isomers of vic-Amino Alcohols - Olofsson, Berit (KTH, Kemi, 2002)
The first part of this thesis describes a synthetic strategythat provides all eight possible isomers of a given vic-aminoalcohol starting from vinylepoxides. The value of a generalroute is evident, as several isomers are needed ininvestigations of structure-activity relationships forpharmacologically active derivatives, and for optimizing theperformance of chiral ligands containing the amino alcoholmoiety. Vinylepoxides, obtained in high enantiomeric excess, werering-opened both with inversion and retention ofstereochemistry, delivering two diastereomeric amino alcoholswith high regio- and stereoselectivity. Via ring-closure toaziridines and subsequent regioselective ring-opening withsuitable oxygen nucleophiles, the two remaining amino alcoholswere selectively achieved. Within this study, two efficient protocols for theregioselective and stereospecific aminolysis of vinylepoxideshave been presented. Comparedto previous methods, theseprocedures use milder reaction conditions, shorter reactiontimes, generally give higher yields and are applicable to alarger set of substrates. Furthermore, the ring-closure ofvic-amino alcohols to the corresponding N-H vinylaziridines hasbeen investigated. Three routes have been found useful, whichone is preferred depends on substrate and scale. In the second part of the thesis, the synthetic strategy isapplied on the synthesis of Sphingosine and its regio- andstereoisomers. Moreover, a rapid way of determining relativeconfiguration of vic-amino alcohols is described, which shouldbe of substantial use when amino alcohols are formed bydiastereoselective reactions. amino alcohols, vinylepoxides, vinylaziridines, oxazolines,oxazolidinones, ring-opening, regioselective,diastereoselective, sphingosine, configuration, NMRspectroscopy.